The role of zinc in skin physiology - relevance for the pathogenesis and treatment of vitiligo - Marianna Emilia Kaczmarek; Adam Wełniak; Rafał Czajkowski (Termedia Publishing House, 2023)
Zinc is a key micronutrient of the skin, where it is responsible, among others, for regulating the processes of melanocyte proliferation, maturation, and differentiation. Recent research has revealed a possible link between zinc levels and the pathogenesis and severity of vitiligo. Zinc deficiency disrupts the activity of immune system cells, which can lead to autoimmunity, melanocyte destruction, and formation of depigmented patches. Numerous studies have found a statistically significant reduction in zinc levels in sera of patients with vitiligo compared to the healthy population. However, the mechanism by which reduced zinc levels might influence the development and severity of depigmented lesions remains unclear. There is no evidence to suggest any benefits of zinc supplementation in vitiligo patients, there are currently no clear guidelines on whether and how zinc supplements should be used in this population. Further research is needed to determine the potential advantage of combining zinc supplementation with commonly used vitiligo treatments.